Cell and Molecular Biology : concepts and experiments - Karp, Gerald (John Wiley, 2005)
Provides coverage of the concepts of cell and molecular biology, using examples of experimentation to support those concepts. This book is intended for sophomore/junior-level courses in cell biology offered out of biology or molecular and cell biology departments.